UJI KARAKTERISTIK FISIK FORMULASI CLAY MASK EKSTRAK ETANOL DAUN UNGU (Graptophyllum pictum L.Griff) DAN UJI AKTIVITAS ANTIBAKTERI TERHADAP Staphylococcus aureus - Choirun Nisak; Hasriyani, Hasriyani; Bintari Tri Sukoharjanti (Nusantara Hasana Journal, 2025)
Skin problems caused by hormones, dead skin cells, clogged pores due to excess oil, and bacterial infections such as Staphylococcus aureus are known as acne. Antibiotics can cause side effects, so natural alternatives such as purple leaf masks are used because of their content of flavonoids, saponins, and tannins with antibacterial properties. Clay masks work by absorbing oil and cleaning pores. This study aims to determine the effectiveness of purple leaf extract clay mask in inhibiting Staphylococcus aureus and its physical characteristics. Formulations include F0 (0%), F1 (20%), F2 (23%), and F3 (26%) with antibacterial testing using disc diffusion methods and physical characteristics. The best physical results are shown by F2 (23%) because the physical quality of the formula is the best. Antibacterial results showed that F3 (26%) had the largest inhibition zone (9.16 mm), followed by F2 (5.76 mm), and F1 (3.9 mm). Purple leaf clay mask shows potential as an antibacterial against Staphylococcus aureus with F2 (23%) considered the best formulation due to its good inhibitory effect and standard-compliant physical properties.